Job stress, working conditions, and work motivation toward employee performance among non-academic staff at Universiti Kebangsaan Malaysia - A. Hamid, Roslina (2023)
In a competitive business environment, various factors that might play the roles in employee performance such as job stress, working condition, and work motivation could affect the employee's performance. This study aims to investigate the impact of job stress, working condition, and work motivation on employee performance among non-academic staff at Universiti Kebangsaan Malaysia (UKM). For research methodology, this study used random sampling by selecting 270 samples specifically non-academic staff grades N11-N40 to be part of this survey. All data was collected through Google Forms and analyzed quantitatively by using the Pearson correlation through Statistical Package for Sciences (SPSS) version 28 per evaluating the relationship between all the variables. The result found that job stress shows no significant relationship with employee performance (0.026). Next, the working condition shows a significant relationship with employee performance (0.229). Finally, work motivation shows a significant relationship with employee performance (0.715). The implication of these study shows that non-academic staff in UKM believe that job stress does not influence their performance. However, working conditions and work motivation affect their performance. Therefore, it can be suggested that the Management should improve the policies in enhancing performance by managing wellness programs and reward systems that will improve workers performance in the future. Comfortable and ergonomic office furniture also important for maintain performance by comfortable seating, desk, and workstations can help reduce fatigue and discomfort and improve employee performance.